2021
DOI: 10.3390/coatings11020169
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Level of Nitric Oxide in Exhaled Air in Patients Using Acrylic Complete Dentures and with Oral Pathologies

Abstract: The measurement of nitric oxide (NO) in exhaled air is used in diagnostics and monitoring of the pathologies in the respiratory system but also in the oral cavity. Researchers have shown a huge increase of its level in asthma and diseases in the oral cavity. It seems reasonable to research the impact of pathologies in the oral cavity on the level of NO in exhaled air. The purpose of this study was to determine the impact of inflammation in the oral cavity (according to the material of dentures) on the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Physiologically, NO is formed by endothelial nitric oxide synthase (eNOS) in endothelial cells and affects the smooth muscles of blood vessels. It is a regulator of blood flow and pressure [ 19 , 20 , 21 ]. In the inflammatory process, blood cells (neutrophils, monocytes) and endothelial cells of blood vessels activated by antigens (bacteria, viruses, parasites, carcinogens) and endothelial cells release many pro-inflammatory mediators, the overexpression of which causes tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…Physiologically, NO is formed by endothelial nitric oxide synthase (eNOS) in endothelial cells and affects the smooth muscles of blood vessels. It is a regulator of blood flow and pressure [ 19 , 20 , 21 ]. In the inflammatory process, blood cells (neutrophils, monocytes) and endothelial cells of blood vessels activated by antigens (bacteria, viruses, parasites, carcinogens) and endothelial cells release many pro-inflammatory mediators, the overexpression of which causes tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…It is important that check-ups take place regularly and that the patient is under constant dental care. The dentist should carry out hygiene instructions already at the first visit and set an important goal, which is keeping the oral cavity clean and preventing the deposition of denture plaques [14][15][16]. The denture should be cleaned at least twice a day with a soft brush and low-abrasion toothpaste or soap.…”
Section: Introductionmentioning
confidence: 99%
“…The gingival bleeding index according to Ainamo and Bay-GBI was used to assess the clinical condition of the periodontal tissues. In this group of patients, a significantly higher level of exhaled NO was found [66]. However, it is necessary to conduct further studies on patients with pathological conditions in the oral cavity.…”
Section: Oral Cavity Pathologiesmentioning
confidence: 67%
“…Among patients with no gingival bleeding during the examination, the values were low. The value of the concentration of NO in exhaled air increases with the exacerbation of bleeding from the gingival pocket [66]. The study by Kamimura et al also showed the presence of such a relationship-it suggests that oral care can reduce FeNO levels by removing bacteria and plaque and reducing the acidity of the oral environment [63].…”
Section: Oral Cavity Pathologiesmentioning
confidence: 98%
See 1 more Smart Citation